A formação do leitor na educação infantil: da descoberta ao encantamento - Bezerra, Elisangela de Souza [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
In the childhood education context, the pedagogic activities are constantly developing. The moment of the first childhood is crucial for the development of the abilities that the individual will take with him for all his life. Since the child is a historically constructed human being and the result of the experiences with the environment, this current paper aimed to understand the importance of the contribution of the reading in the training of readers in the first childhood, as well as the pedagogical activities that make this experience possible. For this purpose a bibliographic research was used, with theoretical background based on the conception social constructivist from Vygotsky (1978), Jolibert (1994) and Magnani (2001). The search for texts dealing with the issues of reading in early childhood education was made on the website of the EDUCERE event, and from the texts found it was possible to carry out analyzes about the development of this important skill that should accompany all people throughout the journey and should be initiated from the beginning of life. It is expected by this research to highlight the need of the training of the reader since the childhood education so that he can become a critical citizen and social active, as well as reflect the teaching activity in the context of the construction of discovery and enjoying the reading

No contexto da educação infantil as práticas pedagógicas estão em constante desenvolvimento. O momento da primeira infância é crucial para o desenvolvimento de habilidades que o indivíduo levará consigo por toda a sua vida. Tendo em vista a criança como ser historicamente construído e resultado das experiências com o meio, o presente trabalho objetivou compreender a importância das contribuições da leitura na formação do leitor na primeira infância, bem como as ações pedagógicas que possibilitaram esta experiência. Para tanto, utilizou-se uma pesquisa bibliográfica, com referencial teórico embasado na concepção sócio-interacionista de Vygotsky (1978), bem como nos escritos de Rizzoli, (2014) e Magnani (2001). A busca por textos que tratassem das questões da leitura na educação infantil foi feita no site do evento EDUCERE (Congresso Nacional de Educação) e, a partir dos textos encontrados foi possível realizar análises acerca do desenvolvimento dessa importante habilidade que deve acompanhar a todas as pessoas por toda a caminhada e deve ser iniciada desde o início da vida. Espera-se com esta pesquisa evidenciar a necessidade da formação do leitor desde a educação infantil para que se torne um cidadão crítico e ativo socialmente, além de, refletir sobre a ação docente no contexto da formação do gosto e descoberta da leitura
Keywords: Leitura; Educação de crianças; Pesquisa bibliografica; Educação - Estudo e ensino